COVID-19 IN INFLAMMATORY BOWEL DISEASE: SHOULD WE BE MORE CAREFUL WITH THE USE OF SALICYLATES? - Mariana Rolim Fernandes MACEDO; Carlos Arthur Fernandes SOBREIRA; Carola Braz de LAVOR; Camila Ribeiro RÔLA; Ticiana Maria de Lavor ROLIM; Francisco Sérgio Rangel de Paula PESSOA; Milena Santana GIRÃO; Caio César Furtado FREIRE; Ranna Caroline Bezerra SIEBRA; Isabele de Sá Silveira MELO; Marcellus Henrique Loiola Ponte de SOUZA; Lucia Libanez Bessa Campelo BRAGA; et al. (Arquivos de Gastroenterologia, 2024)
ABSTRACT Backgrounds: Fortunately, much has been studied about COVID-19 in patients with inflammatory bowel diseases (IBD). Evidence suggests that these patients do not appear to be at increased risk of severe COVID-19. However, there are still some uncertainties regarding the clinical manifestations of COVID-19 in patients with immune-mediated diseases. Objective: This study aimed to describe the main symptoms of COVID-19 and their frequency in IBD patients and evaluate the impact of the IBD therapeutic drugs on clinical presentation of COVID-19 and to determine factors associated with COVID-19 in this population. Methods: Adult patients with IBD from three tertiary-care public, teaching hospitals in Ceará, Northeastern Brazil, were evaluated during one scheduled appointment from March to December 2020. Patients with possible or confirmed COVID-19 were compared with patients without COVID-19. Furthermore, incidences of each symptom were evaluated based on the use of IBD therapeutic drugs. Results: A total of 515 patients with IBD were included in the study: 234 with CD, and 281 with UC. Of these, 174 patients (34%) had possible/confirmed COVID-19 of whom 156 (90%) were symptomatic. Main symptoms were fever (65%) and headache (65%); gastrointestinal symptoms occurred in one third of patients and were higher than COVID-19 in general population. The factors associated with having COVID-19 were female gender (OR 1.71, 95%CI: 1.17-2.50); contact at home (OR 5.07, 95%CI: 3.31-7.78) and outside the home (OR 3.14, 95%CI: 2.10-4.71) with a case of COVID-19; work outside of the home (OR 1.87, 95%CI: 1.26-2.78); family history of COVID-19 (OR 2.29, 95%CI 1.58-3.33) use of salicylate (OR 1.71, 95%CI: 1.17-4.28); and asthma (OR 7.10, 95%CI: 1.46-34.57). Conclusion: IBD patients at high risk of COVID-19 infection may need to avoid salicylate therapy but further studies are necessary to confirm this association.